2003
DOI: 10.1002/cne.10638
|View full text |Cite
|
Sign up to set email alerts
|

AMPA, kainate, and NMDA receptor densities in the hippocampus of untreated male rats and females in estrus and diestrus

Abstract: Steroid hormones systematically affect numerous neuronal targets, thus influencing, in a permanent or a transitory manner, the way the brain reacts to external and internal stimuli. The hippocampus is an important brain region for learning and memory and the glutamatergic intrahippocampal pathway plays a major role in performing such functions. We applied quantitative in vitro receptor autoradiography to examine how the in vivo hormone milieu affects the densities of AMPA, kainate, and NMDA receptors in the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 66 publications
6
21
0
Order By: Relevance
“…Specifically, males had significantly higher levels of NMDA binding in the dentate gyrus compared to females. In agreement with our finding, another study reported higher levels of NMDA binding in the dentate gyrus of males compared to estrus and diestrus females [59]. Males do have greater synaptic connectivity in the dentate gyrus compared to females [60], which may explain the higher levels of NMDA receptor expression observed in the previous [59] and present studies.…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, males had significantly higher levels of NMDA binding in the dentate gyrus compared to females. In agreement with our finding, another study reported higher levels of NMDA binding in the dentate gyrus of males compared to estrus and diestrus females [59]. Males do have greater synaptic connectivity in the dentate gyrus compared to females [60], which may explain the higher levels of NMDA receptor expression observed in the previous [59] and present studies.…”
Section: Discussionsupporting
confidence: 82%
“…Second, although an increase in excitability could, in theory, account for the increase in NMDAR transmission we and others observe (Woolley et al, 1997), it is difficult to explain how this mechanism could contribute to the delayed increase in AMPAR transmission we observe first at E48 (which is maintained at E72), because AMPARs are not voltage dependent. An obvious mechanism is an increase in expression of AMPARs, an interpretation that is supported by others (Palomero-Gallagher et al, 2003). Whether NMDAR transmission is elevated by increased excitability or through insertion of NMDARs into newly formed synapses as our data suggest requires additional investigation at the level of single synapses.…”
supporting
confidence: 50%
“…The hippocampus of male rats contains significantly more AMPA, kainate, and NMDA receptors than those of female rats. Female rats in diestrus have significantly higher AMPA receptor densities than female rats in estrus [30]. These conflicting data show that morphine potentiation by NMDA antagonists follows a complex mechanism that may depend on the antinociceptive assay used, the pain model, and other factors such as type of antagonist, dose, and gender.…”
Section: Discussionmentioning
confidence: 99%